(untitled) (La Universidad, 2016)
Ceramic compositional analysis has begun to provide critical support in understanding ceramic economy, especially production and distribution strategies, and archaeological typology in Pacific Nicaragua that was previously based primarily on surface decoration. Here it presents preliminary results of an ongoing study exploring the paste composition of Tempisque period (500B.C.–A.D. 250) Izalco-style Usulután and Rosales Zoned Engraved ceramic types from the site of La Arenera. Findings suggest that Rosales wares were produced within Pacific Nicaragua but, based on petrological composition, were likely produced beyond the site itself. Further, all Usulután-like samples were likely produced within Pacific Nicaragua—a contradiction to our original hypothesis that some of the Usulután-like wares were imports from El Salvador and others locally made. Of particular interest is the presence of two discrete compositional paste types for the Nicaraguan-produced Usulután-like wares which indicate distinct and unrelated parent rock (and thus geological and geographical) sources for the clays and inclusions. In the final discussion we explore what the results of this preliminary analysis may intimate about the local ceramic economy of La Arenera and its broader external social connections.